Efficient planar perovskite solar cells using passivated tin oxide as an electron transport layer - Lee, Yonghui (2018)
Planar perovskite solar cells using low‐temperature atomic layer deposition (ALD) of the SnO2 electron transporting layer (ETL), with excellent electron extraction and hole‐blocking ability, offer significant advantages compared with high‐temperature deposition methods. The optical, chemical, and electrical properties of the ALD SnO2 layer and its influence on the device performance are investigated. It is found that surface passivation of SnO2 is essential to reduce charge recombination at the perovskite and ETL interface and show that the fabricated planar perovskite solar cells exhibit high reproducibility, stability, and power conversion efficiency of 20%.